2016
DOI: 10.1093/carcin/bgw065
|View full text |Cite
|
Sign up to set email alerts
|

FGFR2 risk SNPs confer breast cancer risk by augmenting oestrogen responsiveness

Abstract: SummaryThe fibroblast growth factor receptor 2 (FGFR2) locus is the ‘top hit’ in genome-wide association studies for breast cancer. Here, we examine the effect of FGFR2 signalling on transcriptional networks in breast cancer and propose a mechanism for FGFR2 risk single-nucleotide polymorphism function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 46 publications
1
48
2
1
Order By: Relevance
“…Although, the MAP3K1 mutations were more frequently observed in HER2+ breast cancer and FGFR2 variants are reported relevant in ER+ and PR+ breast cancer (Pham et al 2013;Campbell et al 2016), we found no significant association between genetic polymorphisms and histopathological characteristics of the cancer samples. Further studies of other polymorphisms in these genes and the expression profile could elicit essential information because FGFR2 is a tumour suppressor gene amplified and overexpressed in 10-15% of breast tumours (Rebbeck et al 2009;Ahmad et al 2012;Tiong et al 2013) and enhanced FGFR expression may not only be due to genetic alterations but also to epigenetic deregulation at transcriptional and post-translational levels.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Although, the MAP3K1 mutations were more frequently observed in HER2+ breast cancer and FGFR2 variants are reported relevant in ER+ and PR+ breast cancer (Pham et al 2013;Campbell et al 2016), we found no significant association between genetic polymorphisms and histopathological characteristics of the cancer samples. Further studies of other polymorphisms in these genes and the expression profile could elicit essential information because FGFR2 is a tumour suppressor gene amplified and overexpressed in 10-15% of breast tumours (Rebbeck et al 2009;Ahmad et al 2012;Tiong et al 2013) and enhanced FGFR expression may not only be due to genetic alterations but also to epigenetic deregulation at transcriptional and post-translational levels.…”
Section: Discussioncontrasting
confidence: 79%
“…Diverse FGF10, FGFR2 and MAP3K1 gene polymorphisms have already been identified as breast cancer susceptible in various populations (Rebbeck et al 2009;Ripperger 2009;Harlid et al 2012;Jara et al 2013;Murillo-Zamora et al 2013;Pritchard and Hayward 2013;Siddiqui et al 2014;Zheng et al 2014;Campbell et al 2016), and studies on breast cancer genetic background have also been performed in Slovakia (Franeková et al 2007;Zubor et al 2007Zubor et al , 2008Zubor et al , 2014Kasajová et al 2016). Results from these studies emphasised the relevance of several polymorphisms in breast cancer susceptibility and pointed out the importance of an inter-population genetic variability.…”
Section: Introductionmentioning
confidence: 99%
“…The BLCA regulator-target associations are inferred using the R package RTN (Castro et al, 2016b), which is extensively described elsewhere for reconstructing regulatory units for transcriptions factors and upstream regulators (Campbell et al, 2016; Castro et al, 2016a; Fletcher et al, 2013). Briefly, gene expression matrices for a set of samples are used to estimate the associations between a regulator and all potential targets.…”
Section: Star Methodsmentioning
confidence: 99%
“…FGFR2 is overexpressed in 5%‐10% of breast tumors . System biology approach suggests a link between FGFR2 germline variants could reduce a cell's ability to respond to estrogen activation . In contrast, TOX3 expression is highly up‐regulated in luminal breast cancer compared to normal breast tissues or basal‐like tumors .…”
Section: Germline Variation: Transition From the Candidate Gene Appromentioning
confidence: 99%